New Emerging SARS-CoV-2 Virus; Structure, Function, and Bioinformatics Analysis - Hosseinpour, Milad; Safari Dizaj, Reza; Sohrabi, Ehsan; Abbasi Dezfouli, Saba; Khorasanian, Reihane; Zekri, Ali (Journal of Pediatric Nephrology, 2020)
The novel coronavirus, known as a Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), is a single-stranded RNA virus, from which structural and some accessory proteins are encoded. It seems that this newly emerged virus uses the ACE2 receptor to enter the cells in the human body. SARS-CoV-2 undergoes an intense immunological pressure in humans, and this generates mutations to bypass the immune system. Some mutations have been detected in this virus genome, which can induce a change in viral potency. By performing pathway enrichment analysis over those genes and identifying relevant protein-protein interactions (PPIs), we were able to list essential pathways affected in infected cells. In this review, we mainly discuss genetic, intracellular mechanisms, diagnosis and feasible therapeutic targets of this novel coronavirus.